Empirical Study of Information Systems Risk Management in Technology Startups in Indonesia - Kaaffah, Faiz Muqorrir; Winardi, Bambang; Karnoto, Karnoto (West Science Information System and Technology, 2025)
This study investigates the influence of Information System Risk Management (ISRM) and IT Governance on the performance of technology startups in Indonesia, with Digital Innovation serving as a mediating variable. A quantitative approach was employed, collecting data from 140 respondents using a 5-point Likert scale questionnaire. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that both ISRM and IT Governance have significant positive effects on digital innovation, which in turn positively impacts startup performance. Additionally, digital innovation partially mediates the relationship between ISRM, IT Governance, and startup performance. These findings highlight that effective risk management and IT governance, combined with digital innovation, are essential for enhancing the performance and competitiveness of technology startups in Indonesia.